2018
DOI: 10.1111/1365-2664.13111
|View full text |Cite
|
Sign up to set email alerts
|

Using terrestrial haematophagous leeches to enhance tropical biodiversity monitoring programmes in Bangladesh

Abstract: Measuring mammal biodiversity in tropical rainforests is challenging, and methods that reduce effort while maximizing success are crucial for long‐term monitoring programmes. Commonly used methods to assess mammal biodiversity may require substantial sampling effort to be effective. Genetic methods are a new and important sampling tool on the horizon, but obtaining sufficient DNA samples can be a challenge. We evaluated the efficacy of using parasitic leeches Haemadipsa spp., as compared to camera trapping, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 37 publications
3
71
3
Order By: Relevance
“…Our analysis did reveal a difference in mammal detection success between the two types of leeches. It is possible that the larger size of tiger leeches leads to a higher chance to amplify mammalian DNA (see also Weiskopf et al , 2018). We also found a slightly stronger bias in tiger leeches towards larger bodied mammals.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our analysis did reveal a difference in mammal detection success between the two types of leeches. It is possible that the larger size of tiger leeches leads to a higher chance to amplify mammalian DNA (see also Weiskopf et al , 2018). We also found a slightly stronger bias in tiger leeches towards larger bodied mammals.…”
Section: Discussionsupporting
confidence: 54%
“…Recent methodological advances, namely amplicon-based high-throughput sequencing or 'metabarcoding', now also allow the reliable reading of such DNA sources (Abrego et al , 2018). Invertebrate-derived DNA (iDNA) is an offshoot of eDNA, where terrestrial vertebrates can be detected via their DNA that was ingested by invertebrates (Schnell et al , 2012(Schnell et al , , 2015Calvignac-Spencer et al , 2013a, 2013bTessler et al , 2018;Weiskopf et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since the field of iDNA originated, targeted collection followed by iDNA analyses of gut contents has been carried out on different invertebrate taxa such as leeches (Drinkwater et al, 2019;Pérez-Flores, Rueda-Calderon, Kvist, Siddall, & Oceguera-Figueroa, 2016;Schnell et al, 2018;Weiskopf et al, 2018), sand flies (Kocher, De Thoisy, et al, 2017), blow and flesh flies Hoffmann et al, 2018;Lee, Gan, Clements, & Wilson, 2016;Lee, Sing, & Wilson, 2015;Rodgers et al, 2017;Schubert et al, 2015), mosquitoes (Kocher, De Thoisy, et al, 2017), ticks (Gariepy et al, 2012), marine copepods (Meekan et al, 2017), and shrimps (Siegenthaler et al, 2019). This has offered a new and promising tool to complement traditional vertebrate monitoring methods, something of great value in the ongoing biodiversity monitoring efforts (Bohmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The use of eDNA is relatively new but shows considerable promise. Invertebrate-derived DNA (iDNA) approaches using terrestrial hematophagous leeches, in particular, have proven adept at detecting tropical mammals (Schnell et al, 2012; Schnell et al, 2018; Weiskopf et al, 2018). Recently, Abrams et al (2019) showed that combining camera-trapping and iDNA leech data has the potential to improve detection probabilities for tropical mammal species beyond what would be provided by each method independently.…”
Section: Introductionmentioning
confidence: 99%